2022
DOI: 10.7196/sajcc.2022.v38i1.491
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Fundamental Critical Course on knowledge acquisition in Rwanda

Abstract: Background. Emerging critical care systems have gained little attention in low- and middle-income countries. In sub-Saharan Africa, only 4% of the healthcare workforce is trained in critical care, and mortality rates are unacceptably high in this patient population. Aim. We sought to retrospectively describe the knowledge acquisition and confidence improvement of practitioners who attend the Fundamental Critical Care Support (FCCS) course in Rwanda. Methods. We conducted a retrospective study in which we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…10 However, even as this course has grown significantly over almost a quarter of a century, very little analysis of the effectiveness of the course content has been completed. Other than small studies in international settings, [11][12][13][14] little work has addressed formal validation of the course or its content. Despite this, some have recommended the course be adopted universally in a variety of settings including undergraduate medical education 15,16 and nursing staff training.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, even as this course has grown significantly over almost a quarter of a century, very little analysis of the effectiveness of the course content has been completed. Other than small studies in international settings, [11][12][13][14] little work has addressed formal validation of the course or its content. Despite this, some have recommended the course be adopted universally in a variety of settings including undergraduate medical education 15,16 and nursing staff training.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Exposure and training in critical care can, however, increase the knowledge, skills and confidence of doctors. [10] An additional benefit is reported by Haniffa et al, [11] who found that, if doctors and nurses working in resource-limited settings received dedicated training, ICU mortality rates declined from 41% to 18%. Training of primary care physicians will have an impact on the burden and outcomes of patients who are admitted to ICUs in SA.…”
mentioning
confidence: 99%